Revisiting Taksin and Thaksin: unceremonious exits and the making of nostalgia in Thai history - Ngui, Clarence YK (Penerbit Universiti Kebangsaan Malaysia, 2016)
Despite vast research on Thai history, little is written about comparative historical leadership, especially comparison between royalty and commoner. King Taksin (1767-1782) and former Prime Minister Thaksin Shinawatra1 (2001 -2006) share more than a similar-sounding name. Both were partly Chinese and originate from Tak and Chiang Mai respectively peripheral cities far from the capital of old Siam and modern Thailand. Both king and prime minister were very successful initially. They introduced various reforms and changes to the kingdom’s politics and economy. In 1767, Taksin rebuilt the Siamese Kingdom in Thonburi from the ashes of the Burmese sacking of Ayutthaya. Similarly, in 2001, Thaksin restored modern Thailand after the Asian Financial Crisis left the kingdom in an economic mess and tatters. The main argument of this article analyses the reasons for Taksin and Thaksin’s unceremonious exits. Their sudden departures created a vacuum; and with a sense of a “deficient present”; these conditions contributed to the need to revisit the “better times”, and thus the making of nostalgia. Relooking at some historical and contemporary sources, this article traces Taksin and Thaksin, their rise, fall and the nostalgia that surround these two leaders of old Siam and modern Thailand. Comparing an 18th century king with a 20th century prime minister, this article opens the research to re-appraisals of traditional Thai historiography in a more contemporary perspective.